Reduced Graphene Oxide and Its Natural Counterpart Shungite Carbon - Elena F Sheka (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2017)
Large variety of structure and chemical-composition of reduced graphene oxide (RGO) is explained from a quantum-chemical standpoint. The related molecular theory of graphene oxide, supported by large experience gained by the modern graphene science, has led the foundation of the concept of a multi-stage graphene oxide reduction. This microscopic approach has found a definite confirmation when analyzing the available empirical data concerning both synthetic and natural RGO products, the latter in view of shungite carbon, suggesting the atomic-microscopic model for its structure.